2011
DOI: 10.1111/j.1439-0310.2011.01941.x
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Analysis Reveals Behavioral Differences Underlying Female-Biased Predation Risk in Stalk-Eyed Flies

Abstract: Stalk‐eyed flies are classic models of how sexual selection can drive morphological and behavioral elaboration. Exaggerated ornaments born by stalk‐eyed flies could impose locomotor costs and increase susceptibility to predation; however, a previous study determined that behavior, not eye span, was the major influence on predation risk. Despite the importance of behavior, relatively little is known about how these flies avoid and deter predators. We created an ethogram of behaviors and used it to score individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
(73 reference statements)
0
4
0
Order By: Relevance
“…When two individuals display a similar behavioural act in two different contexts, this should not be interpreted as perfectly equivalent. Hence, considering transitions among behavioural acts within a sequence, and not only behavioural repertoire, is important to characterize behavioural interactions (Bakeman & Gottman, 1997;Legendre et al, 2008b;Worthington & Swallow, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…When two individuals display a similar behavioural act in two different contexts, this should not be interpreted as perfectly equivalent. Hence, considering transitions among behavioural acts within a sequence, and not only behavioural repertoire, is important to characterize behavioural interactions (Bakeman & Gottman, 1997;Legendre et al, 2008b;Worthington & Swallow, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…When a tephritid fly encounters a salticid, it usually displays to the salticid, with the result that the salticid either retreats or performs a territorial or courtship display in response (Greene et al 1987; see also Worthington & Swallow (2011) for a non-tephritid fly). This phenomenon has been termed 'predator mimicry', with the argument that the fly mimics the appearance and courtship or territorial displays of salticid predators (Eisner 1985;Greene et al 1987;Mather & Roitberg 1987; see also Rota et al (2006)).…”
Section: Introductionmentioning
confidence: 99%
“…Studies investigating the flight performance trade‐offs between males and females have found minor or no differences in aerial performance (Swallow, Wilkinson & Marden, 2000; Ribak & Swallow, 2007), despite predictions that males should suffer from decreased aerial maneuverability compared with females (Swallow et al ., 2000). Substantiating these results on performance, in staged laboratory interactions with a predator, indicate that males exhibit higher survival when facing a predator than do females (Worthington & Swallow, 2010; Worthington & Swallow, 2011). Reasons for this lack of a trade‐off have largely been attributed to morphological compensation by flight musculature and wing size, with males exhibiting significantly larger thoracic masses (Swallow et al ., 2000; Ribak & Swallow, 2007) and wing sizes (Ribak et al ., 2009b; Husak et al ., 2011; Husak & Swallow, 2011) than females.…”
Section: Discussionmentioning
confidence: 90%